A Validated WISC-V Short-Form to Estimate Intellectual Functioning in Very Preterm Children at Early School Age - Sistiaga, Andone; Garmendia, Joana; Aliri, Jone; Marti, Itxaso; Labayru, Garazi (Frontiers in Psychology, 2021)
Very preterm children (gestational age <32 weeks) frequently show neurodevelopmental difficulties (Inattention/dysexecutiveness) throughout their life-stages. A scarcity of resources, along with this population´s cognitive vulnerability, makes the neuropsychological evaluation of these children both complicated and time-consuming. This study aimed to develop a specific and valid Wechsler Scale for Children-Fifth Edition (WISC-V) short-form to estimate intellectual functioning in this population. Eighty-four very preterm children (39 female; mean age=6.50; SD: 0.06) were assessed with the WISC-V. Short-forms were developed following two independent strategies: a) multiple linear regressions for each index; b) correlational analyses between scores on all administered subtests and Full-Scale IQ. Validity of short-forms was analyzed. A short-form (Vocabulary, Matrix Reasoning, Picture Span, and Symbol Search) that satisfied 2/3 validation criteria was proposed. This validated short-form could facilitate the identification of cognitive difficulties in very preterm children, so that they could benefit from early care and support services, avoiding long assessment procedures.